Symptomatic ileofemoral deep vein thrombosis due to May-Thurner syndrome. (9th January 2014) - Alirhayim, Zaid; El Atrache, Mazen; Rocco, Nicole; Drake, Sean
Abstract : A 33-year-old woman with no medical history reported an acute onset of left leg and thigh swelling. A review of her medications revealed that she had started oral contraceptives 2 months previously. Ultrasonography and subsequent venography demonstrated extensive ileofemoral clot burden. Thrombolysis and thrombectomy successfully restored venous return with subsequent improvement in the leg swelling and oedema. In this case, we describe a patient presenting with extensive ileofemoral deep vein thrombosis, otherwise known as the May-Thurner syndrome.